Curcumin delivery using novel chitosan-polyethylene glycol diacrylate microencapsulation prepared via radiation-induced crosslinking - Chaichan Maneerattanarungroj, Prattana Lopin, Chakkraphong Khonthun, Patcharin Jaikhor, Surisak Prasarnpun, (Journal of Applied Pharmaceutical Science, 2022)
The objective of this research is to prepare the shell of a curcumin- (CU-) loaded microcapsule by gamma radiation-induced crosslinking between chitosan (CS) and polyethylene glycol diacrylate (PEGDA) for CU delivery. The CS–PEGDA beads were irradiated by a gamma ray at 25 kGy. With confirmation by Fourier transform infrared spectroscopy, the CS–PEGDA microcapsules were successfully synthesized. The yield of irradiation-induced synthesis of CS–PEGDA was 43.94%. The particle size of the beads observed under electron microscopy varied between 60 and 150 μm (x¯90 ± 18.50 μm), with 25.70% of the pores on the surface and a swelling degree of 110.48%. CU was encapsulated within the CS–PEGDA beads affording a yield of 92.6%. The CS–PEGDA beads were more durable to the razor-cutting force than the CS beads and maintained their spherical morphology. A CU release study from the loaded CS–PEGDA beads under simulated gastrointestinal conditions revealed gradual, sustained release with a constant rate of 10%–20% over 6 hours. Our results suggest that the CS–PEGDA crosslinking process enabled by gamma irradiation could potentially be applied to the encapsulation of CU for effective drug delivery by oral administration.
Keywords: Chitosan-polyethylene glycol diacrylate, gamma radiation-induced crosslinking, curcumin delivery